Back Cover: Taming Metal/Fluorine Carbenoids (Chem. Eur. J. 11/2017). Issue 11 (4th January 2017) - Molitor, Sebastian; Feichtner, Kai‐Stephan; Gessner, Viktoria H.
Abstract : Metal/Fluorine carbenoids are usually highly reactive and temperature‐sensitive compounds. It has now been demonstrated that even these compounds can be stabilized and isolated at room temperature. Manipulation of the strength of the metal–fluorine interaction turned out to be decisive for stability control. As such, the lithium compounds are considerably more reactive than their heavier congeners, which thus also provides a tool for reactivity control. More information can be found in the Communication by V. H. Gessner et al. onpage 2527 ff.